Reformulation of Diversion Regulations as a Justice-Based Child Protection Effort - W. Erfandy Kurnia Rachman; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. The juvenile criminal justice system in Indonesia affirms the protection of children's rights through a restorative justice approach and the use of diversion mechanisms as regulated in the Juvenile Criminal Justice System Law (UU SPPA) and Supreme Court Regulation (PERMA) No. 4 of 2014. However, its implementation still faces obstacles due to the limitation that diversion may only be applied to offenses carrying a penalty of less than seven years. This restriction prevents child offenders involved in crimes with higher penalties (such as in the Ambon statutory rape case) from obtaining access to non-formal settlement mechanisms, thereby exposing them to psychological pressure, social stigma, and outcomes that contradict the principle of the best interests of the child and child protection standards under the Convention on the Rights of the Child. The purpose of this study is to identify and analyze the current diversion regulations as a child protection measure, to evaluate their weaknesses, and to formulate a justice-based reformulation of diversion regulations to strengthen child protection. The approach method used in the preparation of this thesis is Normative Legal Research. The specification of this study is descriptive-analytical. The theories employed include the Theory of Legal Protection, the Legal System Theory, and the Theory of Justice. The results of this study are as follows: (1) Diversion regulations provide a foundation for child protection through a restorative approach; however, limiting diversion based on the severity of the criminal penalty binds law enforcement officials to formal restrictions without allowing them to consider the child's circumstances comprehensively. This is evident in the Ambon case, where the offender was still subjected to formal judicial proceedings because the applicable sentence exceeded seven years, resulting in the failure to achieve educational, restorative, and stigma-prevention goals. (2) Although diversion regulations under the Juvenile Criminal Justice System Law (UU SPPA) are intended to protect children, they still contain weaknesses in terms of substance, structure, and legal culture, which hinder their optimal implementation. Rigid normative limitations, inadequate capacity and coordination among law enforcement officers, and a strong retributive mindset in society prevent the realization of restorative resolutions that align with children's developmental needs. (3) Reformulating diversion is necessary because the current normative restrictions—permitting diversion only for offenses punishable by less than seven years—are inconsistent with the principles of justice, non-discrimination, and the best interests of the child. Expanding the scope of diversion to prioritize recovery and guidance will ensure that the law functions not merely according to its text, but also by considering children’s social and psychological conditions and their future, thereby ensuring truly just and meaningful protection.